2019
DOI: 10.3390/d11080122
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Changes in the Structure of Zooplankton Communities to Infer Water Quality of the Caspian Sea

Abstract: The work aimed to study the structural variables of zooplankton to assess the water quality of the Caspian Sea. Studies of zooplankton were conducted in the spring and summer of 2008 and 2010. Abundance, biomass, an average individual mass of a specimen, Shannon Bi, Shannon Ab, Δ-Shannon indices, and Clarke’s W-statistic were calculated for zooplankton. Quantitative variables of zooplankton were the highest in the Northeastern and Northern Caspian, decreasing towards the Middle Caspian. In the Northeastern and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…The basis of zooplankton quantitative variables was formed rotifers Brachionus quadridentatus, cladocerans Evadne anonyx, Podonevadne angusta, Podo vadne camptonyx, Podonevadne trigona, and copepods Acartia tonsa and Calanipeda aqued cis. In terms of abundance, the Shannon diversity index varied from 0.44 to 1.95 bits/i and from 0.51 bits/mg to 2.35 bits/mg [5,6].…”
Section: Description Of Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…The basis of zooplankton quantitative variables was formed rotifers Brachionus quadridentatus, cladocerans Evadne anonyx, Podonevadne angusta, Podo vadne camptonyx, Podonevadne trigona, and copepods Acartia tonsa and Calanipeda aqued cis. In terms of abundance, the Shannon diversity index varied from 0.44 to 1.95 bits/i and from 0.51 bits/mg to 2.35 bits/mg [5,6].…”
Section: Description Of Study Areamentioning
confidence: 99%
“…Sturgeons of the Caspian Sea are benthivorous [2], with about 90% of the world's sturgeon catch currently being carried out in the Caspian Sea [3]. Furthermore, the Caspian Sea is a hotspot of biological diversity [3][4][5][6]. Biodiversity conservation is an important direction of life science, and its significance has formed the basis of many international documents, including the Convention on Biological Diversity [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The informativeness of biological assessment methods is because the structure of natural communities is formed under the influence of a complex of climatic and anthropogenic factors. In particular, an increase in nutrient load is accompanied by an increase in the abundance and a decrease in the average size of planktonic invertebrates [11][12][13], as well as a violation of the structure of the dominance of species in communities [14][15][16][17]. The effectiveness of the bioindication method based on aquatic invertebrates in environmental studies has been shown in several publications [18][19][20].…”
Section: Introductionmentioning
confidence: 99%